Inspiratory muscle training improves performance of a repeated sprints ability test in professional soccer players. Issue 3 (July 2019) - Cavalcante Silva, Rodrigo Luis; Hall, Elliott; Maior, Alex Souto
Abstract: Background: Inspiratory muscle training (IMT) is an important method of attenuating both respiratory and peripheral effort perceptions, consequently improving neuromuscular performance and resulting in greater improvements in exercise capacity than exercise training alone. Objective: The aim of this study was to investigate the effects of IMT on exercise tolerance, repeated sprint ability (RSA) performance, maximal inspiratory pressure (MIP), and peak inspiratory flow (PIF) in a cohort of professional male soccer players. Methods: Twenty-two healthy male professional soccer players (18.3 ± 1.4 years; 174.5 ± 6.1 cm; 70.5 kg ± 4.6 kg; body fat 10.1 ± 4.2%) from a club in the Brazilian first division soccer league participated in this study. IMT consisted of 15 and 30 self-paced inspiratory breaths (each to 50% maximal static inspiratory pressure [P 0 ]) in the 1-and 2-week intervention period, respectively. IMT was performed prior to soccer training (1 sets.d −1 ; 6 d.wk −1 ) with repeated sprint ability (RSA) assessed pre- and post- the 2-week period of IMT. Results: Statistical analyses identified a significant (p < 0.001) decrease in sprint time post-IMT. Additionally, RSAbest, RSAmean, total sprint time and percentage of RSA performance decrement (RSA % dec ) also showed significant decreases (p < 0.0001) post-IMT. Additional measures including MIP and PIF were also significantly elevated (p < 0.0002) following the 2-week period of IMT. Conclusion: In conclusion, our results raise two important issues. Firstly, IMT demonstrated enhanced inspiratory muscle strength in professional soccer players. Secondly, this increase in inspiratory muscle efficiency led to a decrease in sprint time and improved exercise tolerance. We recommend that a standard training protocol be developed and tested in an experimental and control group with a large representative sample.